The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/21655979.2022.2063592
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG10 suppresses the development of doxorubicin resistance by downregulating miR-302b in triple-negative breast cancer

Abstract: Unlike other types of breast cancer, triple negative breast cancer (TNBC) does not respond to therapies targeting human epidermal growth factor receptor-2 (HER2) or hormone therapy, and the prognosis of patients with TNBC is usually poor. The role of long non-coding RNA (lncRNA) small nucleolar RNA host gene 10 (SNHG10) has been investigated in many types of cancer, but its role in TNBC is unknown. This study aimed to explore the role of SNHG10 in TNBC in the context of doxorubicin treatment, a common therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Adriamycin resistance is prevented from developing in triple-negative BC by upregulating the expression of miR-302b via methylation. 91 MiR-302b cannot considerably slow the growth of triple-negative BC on its own. MiR-302b affects various molecular processes, including DNA repair, cell cycle, and stemness, to improve the response to cisplatin.…”
Section: Role Of Mir-302/367 Cluster In Drug Sensitivity and Resistancementioning
confidence: 98%
See 3 more Smart Citations
“…Adriamycin resistance is prevented from developing in triple-negative BC by upregulating the expression of miR-302b via methylation. 91 MiR-302b cannot considerably slow the growth of triple-negative BC on its own. MiR-302b affects various molecular processes, including DNA repair, cell cycle, and stemness, to improve the response to cisplatin.…”
Section: Role Of Mir-302/367 Cluster In Drug Sensitivity and Resistancementioning
confidence: 98%
“…It can also improve the sensitivity of triplenegative BC to cisplatin by controlling the E2F family-negative1 genome-wide transcriptome analysis and integrin subunit alpha 6 axis. 92 MiRNAs can control oncogenic pathways, which are crucial for the development of tumors; whether they are overexpressed or otherwise dysfunctional, 91 many studies have identified miR-302/ T A B L E 1 MiR-302/367 cluster is aberrantly expressed in different diseased tissues or cells, thus playing an important role in repressing target genes or participating in the regulatory axis. 93 Given that miR-302b-3p binds PTEN to activate the AKT pathway and that miR-302b-3p inhibition blocks PTEN/AKT pathway-related neuronal damage, it is possible that miR-302b-3p is a key target for ISOinduced neuronal injury.…”
Section: Role Of Mir-302/367 Cluster In Drug Sensitivity and Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…LncRNA SNHG10 was downregulated in triple negative breast cancer (TNBC) cells after DOX treatment, and overexpression of SNHG10 significantly promoted DOX-induced apoptosis. Mechanism research showed that SNHG10 could inhibit the development of resistance to DOX by upregulating miR-302b through methylation modulation ( Aini et al, 2022 ).…”
Section: Apoptosismentioning
confidence: 99%